Exploring authorial voice in English language medical journal abstracts in the age of AI - Katalin Doró (Language Value, 2025)
Authorial voice in medical journal abstracts has been widely studied; however, there is a clear research gap concerning how Hungarian authors place themselves in their English-language abstracts. This study examines the differences in the authorial voice used by Hungarian authors publishing in a local journal and international authors publishing in widely read journals. One hundred abstracts on COVID-19 from three journals were extracted and searched for personal pronouns, possessive determiners, noun phrases indicating implicit authorial presence and passive voice. The results suggest a similar frequency of the personal pronoun we across the corpora, but a more frequent use of the possessive determiner our by Hungarian authors, whereas first-person singular pronouns are almost non-existent. While noun phrase usage shows the most variability in the Hungarian abstracts, the passive voice ratio is between those found in the two international corpora. Pedagogical implications are drawn, especially concerning the observation of published abstracts as models for L2 academic writing versus the growing tendency to use artificial intelligence to generate abstracts.